KERAWANG GAYO DAN GEOMETRI - Zulmaulida, Rahmy; Saputra, Edy (ALGORITMA: Journal of Mathematics Education, 2024)
Gayo cultural diversity and the development of geometry concepts as a branch of mathematics can be collaborated through ethnomathematics. This research aims to see and study Kerawang Gayo's work in geometry. This study uses a qualitative approach to ethnography. The research was carried out in the city of Takengon, with the subject of the study being Kerawang Gayo's carving. The instruments used are non-test instruments such as interviews and observation sheets. The data analysis technique in this study goes through several processes, namely: a) data collection; b) reduction; c) presentation of fan data; and d) drawing conclusions. The results of the study showed that there were several motifs found, namely Upuh Ulen-Ulen, Pucuk Rebung, Mata Itik, Leladu, Tulen Ikan, Seisrung, Puter Tali, Gegaping, panah, motif peger, and rante. The motif contains geometric elements such as rectangles, rhombuses, circles, triangles, ellipticals, and straight lines.